2020
DOI: 10.3389/fneur.2020.554032
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Brain Function Networks in Patients With Amnestic Mild Cognitive Impairment: A Resting-State fMRI Study

Abstract: Patients with amnestic mild cognitive impairment (aMCI) are at high risk of developing dementia. This study used resting-state functional magnetic resonance imaging (rs-fMRI) and an independent component analysis (ICA) approach to explore changes in functional connectivity (FC) in the default mode network (DMN), executive control network (ECN), and salience network (SN). Thirty patients with aMCI and 30 healthy controls (HCs) were enrolled. All the participants underwent an rs-fMRI scan. The brain FC in DMN, E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 58 publications
1
9
0
Order By: Relevance
“…It plays a crucial role in the progression of AD ( Greicius et al, 2004 ). Consistent with our findings, numerous studies reported a typical disruption of the DMN in patients with AD and aMCI ( Li et al, 2020 ; Ma et al, 2020 ). Actually, the deposition of β-amyloid proteins occurs in the DMN and might reduce the connection with other brain regions ( Wang et al, 2013 ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…It plays a crucial role in the progression of AD ( Greicius et al, 2004 ). Consistent with our findings, numerous studies reported a typical disruption of the DMN in patients with AD and aMCI ( Li et al, 2020 ; Ma et al, 2020 ). Actually, the deposition of β-amyloid proteins occurs in the DMN and might reduce the connection with other brain regions ( Wang et al, 2013 ).…”
Section: Discussionsupporting
confidence: 93%
“…Resting-state functional MRI (rs-fMRI) is a supplement to sMRI, which can describe functional changes in the whole brain ( Zhang et al, 2020 ). The impairment of functional brain activity occurred mainly in the default mode network (DMN), executive control network (ECN), and salience network (SN) in aMCI ( Li et al, 2020 ; Fu et al, 2021 ; Xue et al, 2021a ). Liu et al (2021) suggested that the impairment of functional brain activity occurred mainly in the DMN and language network in MCI.…”
Section: Introductionmentioning
confidence: 99%
“…However, among the studies included in the analysis, there was one study that reported increased FC of the SN of the left anterior insula in aMCI, compared with HCs. Only one coordinate was available, and thus, the ALE analysis was not conducted in this group (Li X. et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…This indicates that WMH burden plays a more central role in the expression of the SN when the profile is of the amnestic type. Integrity of the SN supports memory performance ( Andreano et al, 2017), but studies characterising the SN profile in aMCI have led to conflicting findings, with some studies indicating reduction (He et al, 2014) and others reporting increases (Li et al, 2020) in SN expression. Although we found significant main effects of "subtype" and "WMH load", indicating that aMCI patients and patients with a low WMH load have reduced regional expression of the SN, these were superseded by a significant effect of the interaction.…”
Section: Discussionmentioning
confidence: 99%